Methodological Transformations in Contemporary Islamic Studies: Trends, Challenges, and Future Directions - Annaprimadonita (Sinergi International Journal of Islamic Studies, 2024)
This narrative review examines recent methodological developments in Islamic Studies, focusing on how traditional epistemologies intersect with contemporary research practices. The study aims to analyze key innovations and contextual influences shaping the evolution of methodology in education, finance, exegesis, and environmental ethics. Literature was collected from multiple academic databases including Scopus, SpringerLink, Google Scholar, and Web of Science using targeted keywords such as "Methodology in Islamic Studies" and "Interdisciplinary Islamic Research." Selection criteria emphasized peer-reviewed works published in the last 15 years with methodological transparency and relevance to Islamic epistemology. Findings indicate a growing trend toward methodological pluralism, with themes including multicultural integration in Islamic pedagogy, expanded interpretive authority in Qur'anic studies, empirical approaches in Islamic finance, and ethical models addressing global crises. These developments reflect a significant departure from rigid traditionalism and a move toward inclusive, data-informed, and socially engaged Islamic scholarship. The study discusses how socio-cultural contexts and institutional policies influence methodological choices, revealing gaps in digital integration and participatory research. It recommends broader adoption of interdisciplinary, technology-enhanced, and community-rooted approaches. The review concludes that sustainable progress in Islamic Studies will depend on strategic reforms in educational policy, cross-sector collaboration, and an ongoing commitment to methodological innovation.